Illustrare la parodia: ‘Rutzvanscad il giovine’, i disegni di Gaetano Gherardo Zompini e il ruolo di Anton Maria Zanetti il Vecchio - Lucchese, Enrico (Drammaturgia, 2021)
The article presents nine unpublished drawings (Venice, Biblioteca nazionale Marciana) that were used for the engraved plates of the libretto (published by Giuseppe Bettinelli in Venice in 1737) of Rutzvanscad il giovine by Zaccaria Valaresso. It was a successful tragedy-parody staged for the first time in Bologna in 1724 and revived several times in Venice (including at the Teatro San Samuele in the 1743 Carnival). The drawings can be attributed to the Venetian artist Gaetano Gherardo Zompini, confirming earlier scientific hypotheses based on the study of the final engravings. The new series is bound at the end of a deluxe copy of the libretto of this successful dramma per musica, which was already in the collection of the patrician bibliophile Giacomo Soranzo, dedicatee of the first volume of Metastasio’s Opere drammatiche (Venice, Giuseppe Bettinelli, 1733) where two headings reused in the Rutzvanscad appear. The great Venetian connoisseur Anton Maria Zanetti the Elder found in Zompini, an artist of modest means of expression, a perfect collaborator in at least three graphic projects in which reality and fiction are wittily and intelligently mixed: Le arti che vanno per via nella città di Venezia and some pastiches taken from real and supposed inventions of Grechetto. Finally, Zanetti’s name is linked to the album of caricatures of the Giorgio Cini Foundation in Venice (and to its twin in Windsor formerly belonging to the Consul Joseph Smith), where situations and images of Rutzvanscad find further echoes.